2020
DOI: 10.1590/1678-2019-0407
|View full text |Cite
|
Sign up to set email alerts
|

The association of self-reported awake bruxism with anxiety, depression, pain threshold at pressure, pain vigilance, and quality of life in patients undergoing orthodontic treatment

Abstract: The association of self-reported awake bruxism with anxiety, depression, pain threshold at pressure, pain vigilance, and quality of life in patients undergoing orthodontic treatment This study aimed to evaluate whether the presence of awake bruxism was associated with temporomandibular dysfunction symptoms, pain threshold at pressure, pain vigilance, oral health-related quality of life (OHRQoL), and anxiety and depression symptoms in patients undergoing orthodontic treatment. Methodology: This observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
3
21
0
6
Order By: Relevance
“…In the latter, that value of 48% at baseline decreased to 26% after one month 18 . A similar AB frequency was found in another study, 49% of the sample (114 patients) beginning orthodontic treatment self‐reported awake bruxism behaviour 27 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the latter, that value of 48% at baseline decreased to 26% after one month 18 . A similar AB frequency was found in another study, 49% of the sample (114 patients) beginning orthodontic treatment self‐reported awake bruxism behaviour 27 …”
Section: Discussionsupporting
confidence: 82%
“…18 A similar AB frequency was found in another study, 49% of the sample (114 patients) beginning orthodontic treatment self-reported awake bruxism behaviour. 27 When the frequency of AB behaviour was analysed between groups, there was no significant variation in this frequency comparing each period to the baseline data (Table 3). Therefore, the in SB after the first and third months of treatment has been reported, 14 in contrast to another study which revealed that, after the first month of treatment, the patients showed a significant reduction in the number of SB episodes, and after three months, the values returned to baseline levels.…”
Section: Discussionmentioning
confidence: 95%
“…Ademais, é imprescindível entender que tanto o bruxismo quanto a ansiedade são problemas que causam alterações na qualidade de vida. Sendo o bruxismo um fenômeno regulado principalmente pelo sistema nervoso central e influenciado por fatores periféricos, que ocasiona desgaste dentário decorrente do aperto e ranger dos dentes, e a ansiedade, que torna-se patológica quando exacerbada, causando dessa forma, uma situação de alerta em demasia, acarretando prejuízo ao indivíduo, sendo citada na literatura como agente coadjuvante na etiologia do bruxismo (FIRMANI et al, 2015;MACHADO et al, 2020).…”
Section: Discussionunclassified
“…Existem dois tipos de bruxismo, o diurno, mais relacionado com a pressão dentária e o noturno, caracterizado pelo ranger dos dentes de forma inconsciente. Tendo em vista que é uma atividade sem função alguma realizada por músculos mastigatórios, pode ocasionar diversas consequências para os indivíduos que possuem essa condição, o que traz a necessidade de descobrir suas possíveis causas (FIRMANI et al, 2015;KUHN e TÜRP, 2018;CAMOINA et al, 2017;MACHADO et al, 2020).…”
Section: Ansiedade E Bruxismounclassified
See 1 more Smart Citation